Five Faces of Lamaholot Women's Oppression in Three Short Stories of Silvester Petara Hurit (Iris Marion Young Perspective) - Koten, Inosensius Soni; Mulyani, Sri (SUAR BETANG, 2025)
This research is a study of five faces of oppression of Lamaholot women in three short stories by Silvester Petara Hurit, namely “Ina Tonu”, “Mama Eta” and “Pilkades”. Using Iris Marion Young's notion of oppression, the focus of this research is to identify the forms of oppression experienced by women and to understand the mechanisms by which customary, religious and government institutions practice this oppression. This research uses a discursive approach with a qualitative interpretation reading method. The results show that in these three short stories there are practices of exploitation, marginalization, powerlessness, cultural imperalism and systemic violence. This oppression is rooted in patriarchal structures, institutional control and cultural stereotypes. Therefore, through these three short stories, Hurit not only describes the reality of gender inequality but also criticizes the oppression experienced by Lamaholot women. In addition, these findings are expected to expand the socio-cultural study of literature and inspire advocacy for gender justice in the Lamaholot community in East Flores.